Use of exercises with increased coordination complexity in the training process of young female volleyball players aged 13-14 years - Boichuk, R.; Iermakov, S.; Nosko, Y. N.; Nosko, Y.; Vaskan, I.; Korop, M.; Kurtova, H.; Grashchenkova, Z (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim In the context of training young female volleyball players, understanding the criteria, extent, and impact of exercises with heightened coordination complexity becomes crucial. This study aims to determine the evaluation criteria, scope, and effects of incorporating exercises with elevated coordination demands on the specific athletic readiness of young female volleyball players aged 13-14 years.